Analisis Dampak COVID-19 Terhadap Harga Saham Bank Syariah Di Bursa Efek Indonesia - Eko Darmawan Suwandi (Politeknik Ganesha Medan, 2022)
This study aims to examine the impact of Covid-19 on the share price of Islamic banks. The research variables used are daily stock price data for Islamic banks for 40 stock trading days before the official announcement of the Covid-19 case in Indonesia and 40 stock trading days after the Covid-19 case was announced. The test results show that there is a difference in the share price of Islamic banks before the announcement of positive cases of Covid-19 in Indonesia and after the announcement of positive cases of Covid-19 in Indonesia, with a significance value of 0.000. After the Covid-19 announcement, it was seen that the share price of Islamic banks fell compared to before the announcement.